Smart cities in India need smart health care - Satyajit Pattnaik (Wolters Kluwer Medknow Publications, 2017)
SMART city project is being implemented with an objective of developing IT enabled services for the people. With this there is a need to improve the health status of the city dwellers, especially the urban poor. This can be achieved by providing SMART (specific, mobile, affordable, referral linkage and timely) health care in the urban areas.